Internalization of Students’ Scientific Attitudes through Islamic Education in Madrasah Aliyah - Sukino, Sukino; Failasufah, Failasufah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
Islamic Education becomes an important subject in maintaining moral and character. This study aims to see the extent to which internalization of the students’ scientific attitude in Madrasah Aliyah (Islamic Senior High School) through Islamic Education. The qualitative approach is used in this research. The data was collected through interview, observation, and documentation. The data was then analyzed to see how the process of the internalization of the scientific attitude works. Based on the result of the study, it is found that the process of scientific attitude internalization carried out through scientific approach, especially in the Qur'an Hadith subject, has formed a critical and democratic attitude. The Fiqh subject forms discipline and responsibility. The Islamic cultural history subject forms an open-minded and critical attitude. Meanwhile, learning Aqidah Akhlak forms honesty, discipline, and democratic attitudes. The implication of this research lies in the strengthening the Islamic education teachers’ understanding in shaping the students’ scientific attitude, so that the students can face contemporary religious problems critically, democratically, and responsibly and become part of the solution for modern Muslim societies.